Pemetaan Spesies Asing Invasif Hydrocotyle leucocephala Cham. & Schltdl. di Kebun Raya Bogor - Fifi Mar’atun Solihah; Muhammad Rifqi Hariri; Turhadi Turhadi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The presence of undocumented alien flora threatens Indonesia’s flora richness and diversity due to unpredictable invasion risks. Hydrocotyle leucocephala is an alien flora that has been reported as invasive in Sri Lanka and Nigeria and has distributed to Indonesia. Therefore, mapping the distribution and describe the morphological of Hydrocotyle leucocephala is necessary to detect the initial introduction or further spread of this species. The data collection was carried out by exploring the Bogor Botanical Gardens. Environmental factors are measured and documented where Hydrocotyle leucocephala occurs. For observation, Hydrocotyle leucocephala was taken and their morphology described. As a results, Hydrocotyle leucocephala was spread over vak V.L, V.G, V.M, IX.D, VIII.B and parking lot near the conservation building in the Bogor Botanical Gardens. It is also known that Hydrocotyle leucocephala is a creeping herbaceous plant with glabrous stems, kidney-shaped leaves, white flowers without petals and green fruit with persistent styles.